1, 3-Propanediol Production from Crude Glycerol by Klebsiella pneumoniae - Jiaxin Wu (Science Faculty of Chiang Mai University, 2019)
Crude glycerol is a major byproduct of biodiesel manufacture, and can be fractionally distilled. We present here the microbial conversion of crude glycerol into 1, 3-propanediol by Klebsiella pneumoniae under micro-aerobic conditions. We evaluated the effects of pure and crude glycerol on microbial growth and resulting product through batch culture fermentation. In addition, we studied effect of fatty acid and methyl ester on fermentation. Comparison of final concentrations and 1, 3-propanediol molar yields indicate that the crude glycerol from biodiesel production can be used as cheap raw material in the production of 1, 3-propanediol by Klebsiella pneumoniae. Using pure glycerol, concentration reaches 81.10 g/L and yield is 0.62 mol/mol, while crude glycerol from biodiesel production yields 76.85g/L concentration and 0.57mol/mol yield. Fatty acid shows itself favorable for 1, 3-propanediol production, while methyl ester causes strong inhibition of 1,3-propanediol production.